Downregulation of Wnt signaling by sonic hedgehog activation promotes repopulation of human tumor cell lines - Jingjing Ma (Disease Models & Mechanisms, 2015)
Tumor repopulation after radiotherapy is a big obstacle for clinical cancer therapy. The molecular mechanisms of tumor cell repopulation after radiotherapy remain unclear. This study investigated the role of sonic hedgehog (SHH) and Wnt signaling pathways in tumor repopulation after radiotherapy in an in vitro repopulation model. In this model, irradiated dying tumor cells functioned as feeder cells, whereas luciferase-labeled living tumor cells acted as reporter cells. Proliferation of reporter cells was measured by bioluminescence imaging. Results showed that irradiated dying HT29 and Panc1 tumor cells significantly stimulated the repopulation of living cells in their respective cultures. In HT29 and Panc1 cells, radiation significantly inhibited Wnt activity. In the irradiated dying HT29 and Panc1 cells, the level of the activated nuclear β-catenin was significantly decreased. Treatment with the Wnt agonist 68166 significantly decreased, whereas treatment with Wnt antagonist significantly increased, repopulation in HT29 and Panc1 tumor cells in a dose-dependent manner. β-catenin short-hairpin RNA (shRNA) also significantly promoted tumor cell repopulation. The level of secreted frizzled related protein-1 (SFRP1), hedgehog and Gli1 were increased in irradiated cells. Our results highlight the interaction between Wnt and SHH signaling pathways in dying tumor cells and suggest that downregulation of Wnt signaling after SHH activation is negatively associated with tumor repopulation.